Assessing the mean reversion behaviour of fiscal policy: the perspective of Asian countries - Lau, Evan; Baharumshah, Ahmad Zubaidi (Routledge, 2009)
This article investigates fiscal policy sustainability in 10 Asian countries by adopting a battery of unit root tests. Univariate unit root tests reveal that the fiscal stance in these countries follows a nonstationary process while the opposite conclusion was drawn for the same dataset using the commonly employed panel unit root techniques. By utilizing the series-specific panel unit-root test recently developed by Breuer et al. [2002, SURADF (Seemingly Unrelated Regression Augmented Dickey-Fuller)] that allows testing for the presence of nonstationarity within individual cross sections of the panel, we found that only cross sections four out of 10 countries in the panel are stationary. This means that fiscal deficits in most Asian countries are in violation of their intertemporal budget constraint and that the deficits are too large.